North Bali Students’ Online Learning Self-Efficacy, Engagement, and Satisfaction - Suryandani, Putu Dinia; Santosa, Made Hery (Vision: Journal for Language and Foreign Language Learning, 2021)
This study aimed to investigate the relationship among online learning self-efficacy, engagement, and students’ satisfaction in online learning. The design of this study was mixed-method research through surveys and open-ended interview with the purposive sampling technique. The quantitative data were analyzed using multiple regression. The respondents were 24 postgraduate students from North Bali, Indonesia. The quantitative data were analyzed using correlation and regression techniques, and an open-ended interview was conducted. The research results showed a positive correlation between online learning self-efficacy, engagement, and students’ satisfaction. The study concludes that students’ satisfaction can be enhanced by increasing students’ online learning self-efficacy and engagement either individually or simultaneously. The implication of this study revealed that strategies in self-efficacy and engagement during learning-related emotions could play a mediating role in academic satisfaction. Additionally, learning-related emotion impacts the metacognitive learning procedures, which thus intervene the impact of satisfaction in online learning.